Publication models and how to choose the right journal - Tony George Jacob; Peush Sahni (Indian Journal of Rheumatology)
A key step in publishing one's manuscript is selecting the journal. If not done right, your work could lose its relevance. There are numerous factors that you may consider in choosing an appropriate journal for your manuscript and these have been listed out in this article. These include journal metrics, reputation, audience, the range and type of articles that the journal covers, turnaround time, its circulation and reach, and the business model of the journal. We, in this article, have covered certain important metrics of a journal like an impact factor, citation index, rejection rate, and the Eigen factor. We have also described the business models that govern scientific publication today – both the traditional and the open-access model – in adequate detail, along with their key advantages and disadvantages. We hope that this article would help you make the key decision of finding the right journal for your manuscript.